Malignancies in systemic rheumatic diseases: A mini review - Geng, Zhe; Ye, Cong; Zhu, Xiaojian (Frontiers in Immunology, 2023)
There is an increased risk of many malignancies in patients with systemic rheumatic diseases, adding to the disease burden in the patients, while adversely affecting their quality of life and life expectancy. The risk and types of malignancies can differ by the type of rheumatic diseases. Possible mechanisms linking them are dynamic and complicated, including chronic inflammation and damage in rheumatic disease, inability to clear oncogenic infections, shared etiology and some anti-rheumatic therapies. Although certain disease-modifying anti-rheumatic drugs(DMARDs) have been proved to be potentially carcinogenic, the majority of them were not associated with increased risk of most malignancies in patients with systemic rheumatic diseases.